The Level of Sexual Bullying Behavior Among Early Adult in Kupang City - Nitneo Koeslulat; Marselino K. P. Abdi Keraf; Juliana Marlin Y Benu (Journal of Health and Behavioral Science, 2021)
Adults can do sexual bullying that leads to aspects of sexuality physically or non-physically and occurs repeatedly. This study aims to determine the level of sexual bullying behavior in early adult in Kupang, totaling 373 participants aged 18-25. The hypothesis is that early adult individuals tend to have high sexual bullying behavior. Collecting data using the Likert scale Sexual Bullying - ASBAE and distributed online, then analyzed using descriptive statistical techniques using SPSS 16.0 software and Microfost Excel 2010. The test results show sexual bullying has a Cronbach alpha value in the range of 0.960-0.966. The results showed that early adult individuals in the city of Kupang had sexual bullying behavior and dimensions of sexual bullying tended to be low because the empirical mean was smaller than the theoretical means. Finally, gender also influenced the level of sexual bullying behavior and the dimensions of sexual bullying for early adults.